Revealing the Silent Curriculum in EFL Syllabus Design at Islamic-Based Schools - Nur Annisa Fitri; Nur Aini Shofiya; Nayla Sa’adah; Gita Anggreani; Rahmatul Zahra Maulida; Addilla Nailul Muna; Zaitun Qamariah (Al-Mudarris, 2026)
This study examines the phenomenon of silent curriculum in the design of English as a Foreign Language (EFL) syllabi in Islamic-based schools. It investigates how the limited integration of Islamic values within EFL materials affects students’ moral and spiritual identity formation. Drawing on a structured literature review and qualitative content analysis informed by an Islamic epistemological perspective, the study analyzes journal articles, curriculum documents, and EFL, textbooks published between 2010-2025. The findings identify three main interrelated mechanisms through which the silent curriculum operates: the dominance of Western cultural representation, the exclusion of Islamic epistemological perspectives from pedagogical discourse, and the omission of faith-responsive values in language task design. Collectively, these mechanisms contribute to identify dissonance and weaken the alignment between English instruction and the ethical objectives of Islamic education. To address this structural imbalance, the study purpose a conceptual framework for an Islamic-values-embedded EFL syllabus that integrates culturally contextualized content, epistemic inclusivity, and faith-responsive task design as organizing principles. By reimagining syllabus development through an Islamic epistemological lens. This study contributes to critical language pedagogy and curriculum studies while offering a coherent foundation for future empirical research on identify formation and communicative competence in Islamic educational contexts.